From the individual break to the historical break: an experience working with victims of political repression - Landa, Jaime (Revista de Psicología, 1999)
The Instituto Latinoamericano de Salud Mental y Derechos humanos (ILIAS) was created in 1988 by a group of professionals who have worked in the field of mental health and human rights since the 1980s. Despite the time elapsed, 10 years since its foundation and 9 years of constitutionally constituted government, the demand for care is constantly increasing, either due to lack of prior therapeutic support or due to the vulnerability of these cases to face evolutionary crises, labor insertion or of another nature. Particularly relevant is the impact on the second and third generation, which is expressed in consultations requested long after the repressive act occurred. ILIAS has developed multiple research activities linked to both the clinical area and the psychosocial area, in a permanent attempt to relate individual problems with the associated macrosocial aspects. The work that I am going to present occupies clinical material of therapeutic processes, whose names and data have been modified.